2017
DOI: 10.3390/atmos8020018
|View full text |Cite
|
Sign up to set email alerts
|

The Urban Heat Island Effect and the Role of Vegetation to Address the Negative Impacts of Local Climate Changes in a Small Brazilian City

Abstract: This study analyzes the influence of urban-geographical variables on determining heat islands and proposes a model to estimate and spatialize the maximum intensity of urban heat islands (UHI). Simulations of the UHI based on the increase of normalized difference vegetation index (NDVI), using multiple linear regression, in Iporá (Brazil) are also presented. The results showed that the UHI intensity of this small city tended to be lower than that of bigger cities. Urban geometry and vegetation (UI and NDVI) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 34 publications
2
13
0
3
Order By: Relevance
“…Surface varieties are largely responsible for creating a mosaic of microclimates. In addition to the artificialization of the urban environment, natural issues, such as topography, also establish a direct relationship in the creation of microclimates [6,9,12,35,69,70].…”
Section: Suhi In São Carlosmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface varieties are largely responsible for creating a mosaic of microclimates. In addition to the artificialization of the urban environment, natural issues, such as topography, also establish a direct relationship in the creation of microclimates [6,9,12,35,69,70].…”
Section: Suhi In São Carlosmentioning
confidence: 99%
“…Currently, cities have increasingly aroused the interest of researchers for the quality of life in the urban environment. Concerns about climatic conditions of metropolises have led several scholars to conduct research on this theme [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [5] demonstrate that the urbanization process affects climate at all scales. Several studies have shown strategies to minimize the impact of growth and of urban density on climate using urban planning as a tool to control land usage and coverage, as well as reduce the impact of the urbanization process [6][7][8]16,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. The relation between the urbanization process and climate is complex.…”
Section: Urban Morphology and Climatementioning
confidence: 99%
“…The authors in [5] demonstrate that the urbanization process affects climate at all scales. Several studies have shown strategies to minimize the impact of growth and of urban density on climate using urban planning as a tool to control land usage and coverage, as well as reduce the impact of the urbanization process [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Urban Morphology and Climatementioning
confidence: 99%